Digital Responsibility at the Nexus of Big Tech and Government: Evidence from Transparency Reports - Haswell, Christopher; Whitford, Andrew (Surveillance & Society, 2025)
Transparency reports are public documents released by companies such as Google, Facebook, and Verizon that contain extensive information regarding data privacy. For instance, these reports document the number of times a law enforcement agency requests user information from a specific company. Transparency reports exist at the nexus of a complex “digital responsibility” relationship between “Big Tech” firms and governments that want the data they collect. We offer the only known systematic analysis of US requests for user information; we use data from over 250 transparency reports provided by fifteen companies from 2010 to 2022 to document nearly eleven million legal requests, national security requests, location requests, and users affected by requests. We also review evidence from content analysis of reports from technology companies. The results suggest that the US government has grown ever more dependent on these companies over time, with an average 759 percent increase in requests for information. In sum, the changing nature of US law enforcement and national security requests reveals a “responsibility dilemma” for companies providing the most personalized technology services.